Melville's Bibles - Pardes, Ilana, 1966- (University of California Press, 2008)
Many writers in antebellum America sought to reinvent the Bible, but no one, Ilana Pardes argues, was as insistent as Melville on redefining biblical exegesis while doing so. In "Moby-Dick," he not only ventured to fashion a grand new inverted Bible in which biblical rebels and outcasts assume center stage, but also aspired to comment on every imaginable mode of biblical interpretation, calling for a radical reconsideration of the politics of biblical reception. In "Melville's Bibles," Pardes traces Melville's response to a whole array of nineteenth-century exegetical writings - literary scriptures, biblical scholarship, Holy Land travel narratives, political sermons, and women's bibles. She shows how Melville raised with unparalleled verve the question of what counts as Bible and what counts as interpretation.